Anti-corrosion mass marine concrete and preparation method thereof

Through the combination of modified weakly alkaline anionic resin and regenerated powder, the corrosion and cracking of large-volume marine concrete in the seashore environment is solved, and better corrosion resistance and longer service life are achieved, while reducing production costs and environmental pollution risks.

CN119774956AActive Publication Date: 2025-04-08CHINA CONSTRUCTION WESTERN CONSTRUCTION GROUP NO 8 (SHANGHAI) CO LTD

Patent Information

Application Number
CN202510279543.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

Existing large-volume offshore concrete is susceptible to corrosion by chloride and sulfate ions in the seashore environment, resulting in performance degradation and cracks. The existing anti-corrosion measures are limited in effect and have high production costs.

Method used

The modified weakly alkaline anionic resin and regenerated micropowder are used to modify the weakly alkaline anionic resin through barium salt solution to enhance its ability to adsorb sulfate ions, and reduce hydration and exothermic heat by regenerating the micropowder and reduce crack generation.

Benefits of technology

It significantly improves the anti-chlorine and sulfate ion corrosion properties of large-volume marine concrete, extends the service life, reduces the possibility of cracks, reduces the risk of environmental pollution, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to anti-corrosion large-volume marine concrete and a preparation method thereof, and the large-volume marine concrete is prepared from the following components in parts by mass: 250 to 375 parts of cement, 25 to 100 parts of fly ash, 20 to 40 parts of regenerated micro powder, 1 to 40 parts of modified alkalescent anion resin, 750 to 900 parts of machine-made sand, 900 to 1000 parts of common gravel, 150 to 200 parts of water and 5 to 20 parts of water reducing agent. Compared with the prior art, the prepared large-volume marine concrete has the advantages of being better in corrosion resistance, longer in service life, not prone to cracking and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a corrosion-resistant large-volume marine engineering concrete and a preparation method thereof. Background Art

[0002] With the construction of more and more large-scale marine engineering buildings such as cross-sea bridges, the demand for large-volume marine engineering concrete is increasing, and the corresponding large-volume marine engineering concrete performance requirements are also getting higher and higher. Large-volume marine engineering concrete is one of the most important civil engineering materials in contemporary times. It is an artificial stone made of cementitious materials, granular aggregates, water, and admixtures and admixtures added in a certain proportion, uniformly stirred, compacted, cured and hardened.

[0003] When large-volume marine concrete is used for construction in coastal areas, chloride ions in the soil or seawater will corrode the large-volume marine concrete, penetrate into the surface of the steel bars, reduce the pH value of the steel bars, and destroy the passivation film on the surface of the steel bars, thereby accelerating the corrosion of the steel bars. This not only affects the bonding performance between the large-volume marine concrete and the steel bars, but also accelerates the appearance of cracks in the large-volume marine concrete under load, reducing the effective bearing area of ​​the reinforced concrete. In addition, there are other types of trace corrosive ions in seawater that can cause corrosion damage to large-volume marine concrete. For example, sulfate ions penetrate into large-volume marine concrete from the outside, react chemically with certain components of large-volume marine concrete, and corrode the large-volume marine concrete, causing the performance of large-volume marine concrete to gradually deteriorate. At present, in order to improve the corrosion resistance of large-volume marine concrete, fly ash, air-entraining agent, expansion agent and other substances are usually added into the concrete to change the internal structure of large-volume marine concrete, thereby improving the corrosion resistance of large-volume marine concrete. However, as the service time of large-volume marine concrete increases, chloride ions will continue to migrate into the interior of the large-volume marine concrete, and the anti-corrosion effect will decrease rapidly.

[0004] Due to its large volume, high hydration heat, and complex construction conditions, large-volume marine concrete is prone to cracks, which affects the safety and durability of the structure. When cracks appear in large-volume marine concrete, the performance of large-volume marine concrete is more affected. Large-volume marine concrete is prone to cracks during operation. The main reason is the influence of cement hydration heat. Cement releases a large amount of heat during the hydration process. Due to the large volume of large-volume marine concrete structures, the heat inside the large-volume marine concrete is not easy to dissipate, resulting in a rapid increase in internal temperature. The surface of large-volume marine concrete dissipates heat quickly, resulting in a large temperature difference between the inside and outside. This temperature difference will produce temperature stress. When the temperature stress exceeds the tensile strength of the concrete, it will cause cracks.

[0005] Patent Publication No. CN114751683A discloses a geopolymer material capable of restoring chloride ion curing ability, a preparation method and an application thereof. The geopolymer material comprises the following components by mass percentage: 8-11% fly ash; 33-40% slag; 5-8% metakaolin; 5-8% silica powder; 11-13% quartz sand; 15-17% composite alkali activator; 10-11% water; 1.4-1.8% anion exchange resin; the anion exchange resin is obtained by pre-treatment of D201 macroporous strong base anion exchange resin by alkali solution soaking and grinding, and its particle size is 200-250 meshes. However, the addition of D201 macroporous strong base anion exchange resin will further enhance the internal alkaline environment, and to a certain extent, will reduce the ability to resist sulfate ion corrosion. Moreover, after the geopolymer material is discarded, it releases more alkaline substances, which has a higher risk of pollution to the soil, water and other environments. In addition, D201 macroporous strong base anion exchange resin has a complex production process and a high cost. Compared with ordinary geopolymer materials, its unit cost is higher, which will significantly increase the production cost when used in the preparation of geopolymer materials. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a corrosion-resistant large-volume marine engineering concrete with better corrosion resistance, longer service life and less prone to cracking, and a preparation method thereof.

[0007] The purpose of the present invention can be achieved by the following technical solutions: In one aspect, the present invention provides a corrosion-resistant large-volume marine engineering concrete, which comprises the following components, measured by mass: 250-375 parts of cement, 25-100 parts of fly ash, 20-40 parts of recycled micropowder, 1-40 parts of modified weak alkaline anion resin, 750-900 parts of machine-made sand, 900-1000 parts of ordinary crushed stone, 150-200 parts of water, and 5-20 parts of water reducer.

[0008] Furthermore, the weight fraction of the modified weakly basic anionic resin is preferably 5-40 parts, preferably 5-30 parts, and more preferably 15-30 parts.

[0009] Furthermore, the weakly basic anion resin used is a weakly basic acrylic anion resin, the functional group of which is -NH(CH2CH2NH)2, and the particle size is 0-2.56 mm and does not include 0.

[0010] Furthermore, the weakly basic anion resin used is D315 weakly basic acrylic anion resin.

[0011] Furthermore, the weakly basic anion resin used is subjected to modification treatment before use, and the modification process is: soaking the weakly basic anion resin in a solution containing barium ions, and obtaining a modified weakly basic anion resin after the soaking is completed.

[0012] Furthermore, the barium ion-containing solution includes barium nitrate solution, barium carbonate solution, barium hydroxide solution, barium peroxide solution, barium chromate solution, and barium manganate solution, which are other types of barium salts that can be ionized in water except barium sulfate and barium chloride; The mass concentration of the barium ion solution is 20%-80%.

[0013] Furthermore, the soaking time is 2 to 4 hours, and during the soaking, the barium ion-containing solution immerses the weakly alkaline anion resin.

[0014] Furthermore, after the soaking is completed, the modified weakly basic anion resin is air-dried until the surface is dry.

[0015] Furthermore, the regenerated micropowder has a calcium oxide content of 45%-50%, a silicon dioxide content of 34%-40%, an aluminum oxide content of 5%-10%, an iron oxide content of 2%-5%, and a fineness of 40-50 μm.

[0016] Furthermore, the fly ash is Class II fly ash.

[0017] Furthermore, the machine-made sand is medium-coarse sand, and its fineness modulus is between 2.1 and 3.0.

[0018] Furthermore, the particle size of the ordinary gravel ranges from 5 to 31.5 mm.

[0019] Furthermore, the cement is PO42.5 ordinary Portland cement.

[0020] Furthermore, the water reducer is a polycarboxylate water reducer.

[0021] In another aspect, the present invention further provides a method for preparing a corrosion-resistant large-volume marine engineering concrete, comprising the following steps: S1. Weigh cement, fly ash, recycled micro powder, modified weak alkaline anion resin, machine-made sand, ordinary crushed stone, water and water reducing agent for later use; S2. Stir and mix the weighed cement, fly ash, recycled micro powder, modified weak alkaline anion resin, machine-made sand, ordinary crushed stone and water reducing agent, then add water and stir and mix evenly to obtain corrosion-resistant large-volume marine engineering concrete.

[0022] Furthermore, in step S2, ordinary crushed stone and machine-made sand are first mixed, and then cement, fly ash, regenerated micro powder, and modified weakly alkaline anion resin are added and mixed, and then a water reducing agent and water are added and mixed.

[0023] Compared with the prior art, the present invention has the following advantages: (1) The present invention utilizes barium salt to modify weakly basic anion resin. On the one hand, the weakly basic anion resin effectively utilizes the adsorption characteristics of sulfate ions, adsorbs sulfate ions to the resin and reacts with barium ions to solidify, thereby reducing the number of invading sulfate ions. On the other hand, the precipitate produced by the chemical reaction between sulfate ions and barium ions is used to block the pores inside the concrete, optimize the density of the concrete, and reduce the further intrusion and corrosion of sulfate ions and chloride ions into the interior of the concrete.

[0024] (2) As we all know, C3A (tricalcium aluminate, 3CaO·Al2O3, abbreviated as C3A) generated during cement hydration has the fastest hydration speed, the fastest heat release speed and the largest heat release, and is the largest source of hydration heat generated by large-volume marine engineering concrete. The present invention uses recycled micropowder. The calcium ions in the recycled micropowder can react with the sulfate ions eroded into the concrete with the C3A generated by cement hydration to generate a small amount of AF t (Ettringite, 3CaO·Al2O3·3CaSO4·32H2O, referred to as AF t ), C3A will further compare with the generated AF t Reaction to form AF m (monosulfur calcium sulfoaluminate, 3CaO⋅Al2O3⋅CaSO4⋅31H2O, referred to as AF m ), forming a diffusion barrier on the surface of C3A particles to slow down their hydration reaction. The present invention can effectively reduce the hydration heat of large-volume marine concrete by using recycled micropowder and modified weakly alkaline anion resin, thereby reducing the possibility of temperature cracks in concrete.

[0025] (3) The modified weakly alkaline anion resin in the present invention can also effectively utilize barium sulfate to precipitate and solidify the chloride ions attached to the resin surface, thereby reducing or even preventing the corrosion of the internal concrete by chloride ions, and improving the concrete's resistance to chloride ion corrosion. In addition, the weakly alkaline environment is not conducive to the reaction of corrosive media such as sulfate with the components in the concrete, which can improve the concrete's ability to resist sulfate corrosion to a certain extent and extend the service life of the concrete in the sulfate environment. The addition of the modified weakly alkaline anion resin to the concrete will not effectively increase the pH of the concrete, so it can effectively avoid the strong alkaline resin from bringing about an increase in the alkaline environment inside the concrete and reducing the ability to resist sulfate ion corrosion.

[0026] (4) During the use of modified weakly alkaline anion resin, due to its weak alkalinity, the impact on the environment is relatively small. After the concrete is discarded, it releases less alkaline substances and has a lower risk of pollution to the soil, water and other environments, which meets the environmental protection requirements of modern engineering construction.

[0027] (5) The production process of weak alkaline anion resin is relatively simple, and its raw material price is relatively low. When it is applied to concrete, the overall performance of concrete can be improved at a lower price. It will not significantly increase the cost of raw materials, but can also achieve better corrosion resistance, longer service life, and less prone to cracking. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0029] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.

[0030] Example 1

[0031] A C30 corrosion-resistant large-volume marine engineering concrete comprises, by weight, 240 parts of cement, 60 parts of fly ash, 30 parts of recycled micropowder, 20 parts of modified weakly alkaline anion resin, 800 parts of machine-made sand, 950 parts of ordinary crushed stone, 200 parts of water, and 5 parts of water reducer.

[0032] In this embodiment, the weakly basic anion resin used is a weakly basic acrylic anion resin, whose functional group is -NH(CH2CH2NH)2, and whose particle size is 0-2.56 mm and does not include 0. The weakly basic anion resin used is D315 weakly basic acrylic anion resin, and the manufacturer is Anhui Samsung Resin Technology Co., Ltd.

[0033] In this embodiment, the weakly basic anion resin used is modified before use. The modification process is as follows: the weakly basic anion resin is completely immersed in a barium nitrate solution with a mass concentration of 20% for 3 hours. After the immersion is completed, the resin is air-dried until the surface is dry to obtain a modified weakly basic anion resin.

[0034] In this embodiment, the regenerated micropowder has a calcium oxide content of 45%-50%, a silicon dioxide content of 34%-40%, an aluminum oxide content of 5%-10%, an iron oxide content of 2%-5%, and a fineness of 40-50 μm.

[0035] In this embodiment, the fly ash is Class II fly ash.

[0036] In this embodiment, the machine-made sand is medium-coarse sand, and its fineness modulus is between 2.1 and 3.0.

[0037] In this embodiment, the particle size of the ordinary gravel ranges from 5 to 31.5 mm.

[0038] In this embodiment, the cement is PO42.5 ordinary Portland cement.

[0039] In this embodiment, the water reducer is a polycarboxylic acid water reducer with a water reduction rate of ≥25%, a solid content of >15%, and a pH of 7.1, and is sourced from China Construction Western Construction New Materials Technology Co., Ltd.

[0040] A method for preparing C30 corrosion-resistant large-volume marine engineering concrete comprises the following steps: S1. Weigh cement, fly ash, recycled micro powder, modified weak alkaline anion resin, machine-made sand, ordinary crushed stone, water and water reducing agent for later use; S2. First, put ordinary crushed stone and machine-made sand in a mixer, then add cement, fly ash, recycled micro powder, and weak alkaline anion resin and mix for 30 seconds. Finally, add water reducer and water, mix and stir evenly to obtain C30 fly ash ordinary concrete.

[0041] Example 2

[0042] A C30 corrosion-resistant large-volume marine concrete is the same as Example 1 except that the mass concentration of the barium nitrate solution is adjusted to 40% during the modification of the weakly alkaline anion resin used.

[0043] Example 3

[0044] A C30 corrosion-resistant large-volume marine concrete is the same as Example 1 except that the mass concentration of the barium nitrate solution is adjusted to 60% during the modification of the weakly alkaline anion resin used.

[0045] Example 4

[0046] A C30 corrosion-resistant large-volume marine concrete is the same as Example 1 except that the mass concentration of the barium nitrate solution is adjusted to 80% during the modification of the weakly alkaline anion resin used.

[0047] Example 5

[0048] A C30 corrosion-resistant large-volume marine concrete is the same as Example 3 except that the mass fraction of the modified weakly alkaline anion resin is adjusted to 30 parts.

[0049] Example 6

[0050] A C30 corrosion-resistant large-volume marine concrete is the same as Example 3 except that the mass fraction of the modified weakly alkaline anion resin is adjusted to 25 parts.

[0051] Example 7

[0052] A C30 corrosion-resistant large-volume marine concrete is the same as Example 3 except that the mass fraction of the modified weakly alkaline anion resin is adjusted to 15 parts.

[0053] Example 8

[0054] A C30 corrosion-resistant large-volume marine concrete is the same as Example 3 except that the mass fraction of the modified weakly alkaline anion resin is adjusted to 10 parts.

[0055] Example 9

[0056] A C30 corrosion-resistant large-volume marine concrete is the same as Example 3 except that the mass fraction of the modified weakly alkaline anion resin is adjusted to 5 parts.

[0057] Comparative Example 1 A fly ash ordinary concrete is the same as Example 1 except that the recycled micro powder and the modified weakly alkaline anion resin are not added.

[0058] The preparation method of the fly ash ordinary concrete is as follows: each component is prepared according to mass, ordinary crushed stone and machine-made sand are first placed in a mixer, cement and fly ash are added and mixed for 30 seconds, and finally a water reducer and water are added, and the mixture is mixed and stirred evenly to obtain C30 fly ash ordinary concrete.

[0059] Comparative Example 2 A C30 corrosion-resistant large-volume marine concrete is the same as Example 6 except that the modified weakly alkaline anion resin is adjusted to a weakly alkaline anion resin and the resin is not immersed in a barium ion solution.

[0060] Comparative Example 3 A C30 corrosion-resistant large-volume marine concrete is the same as Example 3 except that the modified weakly alkaline anion resin is adjusted to a weakly alkaline anion resin and the resin is not immersed in a barium ion solution.

[0061] Comparative Example 4 A C30 corrosion-resistant large-volume marine concrete is the same as Example 7 except that the modified weakly alkaline anion resin is adjusted to a weakly alkaline anion resin and the resin is not immersed in a barium ion solution.

[0062] Comparative Example 5 A C30 corrosion-resistant large-volume marine concrete is the same as Example 3 except that the D315 weakly alkaline acrylic anion resin is adjusted to a D201 strongly alkaline anion resin.

[0063] Comparative Example 6 Compared with Example 3, except that the regenerated micro powder is not added, everything else is the same.

[0064] Comparative Example 7 Compared with Example 3, except that the modified weakly basic anion resin is not added, the other steps are the same.

[0065] Comparative Example 8 Compared with Example 3, except that the barium nitrate solution is adjusted to a calcium nitrate solution, everything else is the same.

[0066] The different raw material compositions and dosages of each embodiment and comparative example are shown in Table 1 below.

[0067] Table 1 Differentiated raw material compositions and dosages of various examples and comparative examples

[0068] The performance characterization results of the concrete prepared in each embodiment and comparative example are shown in Table 2.

[0069] The compressive strength of 100mm cube is tested in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (CBT50081-2019).

[0070] The rapid chloride ion diffusion coefficient DRCM and electric flux of concrete were tested in accordance with the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (CB / T 50082-2009).

[0071] According to the immersion corrosion resistance test method (K method) in GB / T1749-2008 "Test method for cement resistance to sulfate attack", the specimens were immersed in fresh water and SO4 2- Soak in solution (SO4 2- The corrosion simulation test was carried out for 12 months in the corrosion solution with a concentration of 20000mg / L). After the immersion, the flexural strength of the specimens was measured and the corrosion resistance coefficient was calculated. The corrosion resistance coefficient ≥ 0.80 was considered qualified and used as the judgment standard.

[0072] According to the "Concrete Physical and Mechanical Properties Test Method Standard" (CBT50081-2019), the concrete adiabatic temperature peak is measured by the concrete adiabatic temperature rise measuring instrument.

[0073] Table 2 Performance characterization results of concrete prepared in various embodiments and comparative examples

[0074] As can be seen from the above table, the concrete specimens of the embodiments of the present invention exhibit good resistance to chloride ion and sulfate corrosion, and maintain good mechanical properties. Among them, by observing Comparative Example 3 and Examples 1-4, it can be seen that the amount of regenerated micropowder and modified weakly alkaline anion resin is controlled unchanged, and the mass concentration of the barium nitrate solution used for modification is adjusted. It is found that as the mass concentration of the barium nitrate solution increases, the strength of large-volume marine engineering concrete can reach or even exceed the strength of ordinary fly ash concrete.

[0075] In addition, compared with fly ash ordinary concrete (Comparative Example 1), the chloride ion penetration resistance and sulfate ion resistance of large-volume marine engineering concrete show a trend of increasing first and then decreasing with the increase of the mass concentration of barium nitrate solution. When the ratio of the regenerated micropowder to the barium salt ions in the modified weakly alkaline anion resin reaches a certain level, the corrosion resistance of the concrete reaches the best, and the best performance in the current embodiments is embodiment 3. Further analysis of the change in the hydration temperature peak of the large-volume marine engineering concrete in embodiment 3 shows that the hydration temperature peak is also greatly reduced compared with the ordinary fly ash concrete. It can be seen that the mass concentration of the barium nitrate solution used for modification has a great influence on the strength, chloride ion penetration resistance, sulfate ion resistance, and hydration temperature peak of large-volume marine engineering concrete. This is because within a certain range, as the mass concentration of the barium nitrate solution increases, the exchange capacity of the weakly alkaline anion resin increases. More barium ions can be combined with the exchangeable groups on the weakly alkaline anion resin, so that the weakly alkaline anion resin can adsorb or exchange more target ions, thereby increasing the number of active sites that can participate in the exchange, thereby increasing the barium ion concentration inside the resin. When the mass concentration of barium nitrate solution is too high, the ion exchange equilibrium may be reversed or the internal steric hindrance of the weak base anion resin may increase. Excessive barium ion concentration will reduce the barium ion concentration gradient around the resin surface, which is not conducive to the continued ion exchange reaction. At the same time, too many barium ions may accumulate inside the resin particles, hindering other ions from approaching the exchangeable sites of the resin, causing the exchange capacity to no longer increase or even decrease, thereby reducing the barium ion concentration inside the resin. The barium ion concentration in the resin will not only affect the amount of barium sulfate precipitate generated, but also affect the concentration of sulfate ions eroded into the concrete, which will subsequently affect the reaction between sulfate ions and C3A produced by cement hydration to generate AF. t , affecting C3A, which will further react with the generated AFt to form AF m , which affects the formation of a diffusion barrier on the surface of C3A particles to slow down their hydration reaction, and finally leads to the generation of concrete hydration heat. And with the increase of the mass concentration of barium nitrate solution, the particle size, pore structure and mechanical strength of the weak base anion resin may be affected during the modification process of the weak base anion resin.

[0076] Observing Example 3 and Comparative Example 8, if the barium nitrate solution is replaced with calcium nitrate, the concrete's ability to resist sulfate and sulfate corrosion and reduce hydration heat will be weakened. Because the volumetric capacity of calcium sulfate is much higher than that of barium sulfate, its solubility in water is strong. Since the sulfate ion content in the marine environment is relatively low, barium sulfate precipitation is generated, but calcium sulfate precipitation is not generated.

[0077] By observing comparative examples 1, 6, 7 and embodiment 3, the effect of adding regenerated micropowder alone on improving the resistance to sulfate radicals, sulfate corrosion and reducing the heat of hydration is relatively small. The effect of adding weakly basic anion resin alone is better than that of adding regenerated micropowder alone, but both are less than the case of adding modified weakly basic anion resin and regenerated micropowder at the same time. When modified weakly basic anion resin and regenerated micropowder are added together, the resistance to sulfate radicals, sulfate corrosion and the ability to reduce the heat of hydration can be effectively and significantly improved, indicating that the addition of modified weakly basic anion resin and regenerated micropowder has a synergistic improvement effect.

[0078] By observing Examples 3, 5 to 8, it can be seen that when the mass concentration of the regenerated micropowder and the barium nitrate solution for modification is fixed, as the amount of the modified weakly basic anion resin increases, the strength of the large-volume marine engineering concrete at each age gradually increases, and the resistance to chloride ions and sulfate ions also increases first and then decreases. It can be seen that the amount of the modified weakly basic anion resin has an important influence on the role of the adsorbed barium ions in the concrete. Within a certain range, the more the amount of the modified weakly basic anion resin is used, the more uniform the distribution in the concrete. When the amount of the modified weakly basic anion resin added is too much, it will affect the density of the internal structure of the concrete, and then affect the resistance to chloride ions and sulfate ions of the concrete. When the amount of the modified weakly basic anion resin reaches a certain optimal dosage, the effect of the adsorbed barium ions is best.

[0079] By observing Example 6 and Comparative Example 2, Example 1 and Comparative Example 3, Example 7 and Comparative Example 4, it is found that when the weakly basic anion resin is not modified, the incorporation of the weakly basic anion resin itself has no better effect on the concrete strength, resistance to chloride ion penetration, resistance to sulfate ion, and hydration temperature peak. And by comparing Comparative Examples 2 to 4 with Comparative Example 7, it is found that the effects of adding unmodified weakly basic anion resin and not adding weakly basic anion resin are consistent, with no obvious difference. It is further explained that when the weakly basic anion resin is not modified, the incorporation of the weakly basic anion resin itself has no better effect on the concrete strength, resistance to chloride ion penetration, resistance to sulfate ion, and hydration temperature peak.

[0080] By observing Example 3 and Comparative Example 5, after the weakly alkaline D315 acrylic anion resin was adjusted to the strongly alkaline D201 anion resin, the anti-permeability and anti-sulfate corrosion performance of the large-volume marine engineering concrete was weakened. If there is sulfate in the environment where the concrete is located, the D201 strongly alkaline anion resin will exchange a large amount of sulfate ions into the concrete, causing the sulfate ion concentration in the concrete to increase rapidly. When all the barium ions in the resin react with the sulfate, the remaining aggregated sulfate ions create more favorable conditions for sulfate to erode the concrete, weakening the anti-permeability and anti-sulfate corrosion performance.

[0081] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A corrosion-resistant large-volume marine engineering concrete, characterized in that: The large-volume marine engineering concrete comprises the following components by weight: 250-375 parts of cement, 25-100 parts of fly ash, 20-40 parts of recycled micropowder, 1-40 parts of modified weakly alkaline anion resin, 750-900 parts of machine-made sand, 900-1000 parts of ordinary crushed stone, 150-200 parts of water, and 5-20 parts of water reducer; The weakly basic anion resin used is modified before use, and the modification process is: soaking the weakly basic anion resin in a barium ion-containing solution, and obtaining the modified weakly basic anion resin after the soaking is completed.

2. The corrosion-resistant large-volume marine concrete according to claim 1, characterized in that: The weakly basic anion resin used is a weakly basic acrylic anion resin, the functional group of which is -NH(CH2CH2NH)2, and the particle size is 0-2.56 mm and does not include 0.

3. The corrosion-resistant large-volume marine concrete according to claim 2, characterized in that: The weakly basic anion resin used is D315 weakly basic acrylic anion resin.

4. The corrosion-resistant large-volume marine concrete according to claim 1, characterized in that: The barium ion-containing solution includes barium nitrate solution, barium carbonate solution, barium hydroxide solution, barium peroxide solution, barium chromate solution, and barium manganate solution; The mass concentration of the barium ion solution is 20%-80%.

5. The corrosion-resistant large-volume marine concrete according to claim 1, characterized in that: The regenerated micro powder has a calcium oxide content of 45%-50%, a silicon dioxide content of 34%-40%, an aluminum oxide content of 5%-10%, an iron oxide content of 2%-5%, and a fineness of 40-50 μm.

6. The corrosion-resistant large-volume marine concrete according to claim 1, characterized in that: The fly ash is Class II fly ash.

7. The corrosion-resistant large-volume marine concrete according to claim 1, characterized in that: The machine-made sand is medium-coarse sand, and its fineness modulus is between 2.1 and 3.

0.

8. The corrosion-resistant large-volume marine concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

9. A method for preparing a corrosion-resistant large-volume marine concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Weigh cement, fly ash, recycled micro powder, modified weak alkaline anion resin, machine-made sand, ordinary crushed stone, water and water reducing agent for later use; S2. Stir and mix the weighed cement, fly ash, recycled micro powder, modified weak alkaline anion resin, machine-made sand, ordinary crushed stone and water reducing agent, then add water and stir and mix evenly to obtain corrosion-resistant large-volume marine engineering concrete.

Citation Information

Patent Citations

  • Geopolymer material capable of recovering chloride ion curing capacity and preparation method and application thereof

    CN114751683A

  • Solvent-free anticorrosive paint composition capable of being solidified in seawater

    CN104231863A

  • Preparation method of modified hydrotalcite-like concrete sulfate-corrosion-resistant preservative

    CN110255963A

  • Method for preparing magnetic material LDH from electroplating sludge in recycling manner

    CN111282965A

  • Permeable pavement concrete and preparation method thereof

    CN118125762A

Cited By

  • Graphene concrete with heat-storage seepage-proofing composite structure and preparation method of graphene concrete

    CN121021069A